Plant Species-Dependent Increased Abundance and Diversity of IncP-1 Plasmids in the Rhizosphere: New Insights Into Their Role and Ecology - Shintani, Masaki; Nour, Eman; Elsayed, Tarek; Blau, Khald; Wall, Inessa; Jechalke, Sven; Spröer, Cathrin; Bunk, Boyke; Overmann, Jörg; Smalla, Kornelia (Frontiers in Microbiology, 2020)
IncP-1 plasmids, first isolated from clinical specimens (R751, RP4), are recognized as important vectors spreading antibiotic resistance genes. The abundance of IncP-1 plasmids in the environment previously reported, suggested a correlation with anthropogenic pollution. Unexpectedly, qPCR-based detection of IncP-1 plasmids revealed also an increased relative abundance of IncP-1 plasmids in total community DNA from the rhizosphere of lettuce and tomato plants grown in non-polluted soil along with plant age. Here we report the successful isolation of IncP-1 plasmids by exploiting their ability to mobilize plasmid pSM1890. IncP-1 plasmids were captured from the rhizosphere but not from bulk soil, and a high diversity was revealed by sequencing of 14 different plasmids that were assigned to IncP-1,  and  subgroup. Although backbone genes were highly conserved and mobile elements or remnants as Tn501, IS1071, Tn402 or class 1 integron were carried by 13 of the sequenced IncP-1 plasmids, no antibiotic resistance genes were found. Instead, seven plasmids had a mer operon with Tn501-like transposon and five plasmids contained putative metabolic gene clusters linked to these mobile elements. In-depth sequence comparisons with previously known plasmids indicate that the IncP-1 plasmids captured from the rhizosphere are archetypes of those found in clinical isolates. Our findings that IncP-1 plasmids do not always carry accessory genes in unpolluted rhizospheres are important to understand the ecology and role of the IncP-1 plasmids in natural environment.